Child protective services utilization of child abuse pediatricians: A mixed methods study. (February 2018) - Girardet, Rebecca; Bolton, Kelly; Hashmi, Syed; Sedlock, Emily; Khatri, Rachna; Lahoti, Nina; Lukefahr, James
Abstract: Several children's hospitals and medical schools across Texas have child abuse pediatricians (CAPs) who work closely with child protection workers to help ensure accurate assessments of the likelihood of maltreatment in cases of suspected abuse and neglect. Since the state does not mandate which cases should be referred to a CAP center, we were interested in studying factors that may influence workers' decisions to consult a CAP. We used a mixed methods study design consisting of a focus group followed by a survey. The focus group identified multiple factors that impact workers' decision-making, including several that involve medical providers. Responses from 436 completed surveys were compared to employees' number of years of employment and to the state region in which they worked. Focus group findings and survey responses revealed frustration among many workers when dealing with medical providers, and moderate levels of confidence in workers' abilities to make accurate determinations in cases involving medical information. Workers were more likely to refer cases involving serious physical injury than other types of cases. Among workers who reported prior interactions with a CAP, experiences and attitudes regarding CAPs were typically positive. The survey also revealed significant variability in referral practices by state region. Our results suggest that standard guidelines regarding CAP referrals may help workers who deal with cases involving medical information. Future research and quality improvement efforts to improve transfers of information and to better understand the qualities that CPS workers appreciate in CAP teams should improve CAP-CPS coordination.